Interaction of chronic pain, obesity and time of day on cortisol in female human adolescents. (2nd January 2022) - Raff, Hershel; Phillips, Jonathan; Simpson, Pippa; Weisman, Steven J.; Hainsworth, Keri R.
Abstract: Adolescent obesity augments and impedes the treatment of chronic pain. This is associated with increased systemic inflammation and is more prominent in females. In addition, pain and obesity each independently affect the hypothalamic-pituitary-adrenal (HPA) axis. However, the interaction of pain and obesity on the HPA axis and the potential for sexual dimorphism in this phenomenon is not established. We hypothesized that dysregulation of the HPA axis occurs in female human adolescents with chronic pain, obesity, or the combination of the two and is associated with gonadal steroids. We measured serum cortisol, estradiol, and testosterone in 13–17-year-old adolescent females ( N = 79) from venous blood drawn during the daytime (0830–1730 h) and analyzed the data in toto and partitioned by morning vs. afternoon sampling time. Subjects were categorized as healthy weight/no pain (controls; BMI = 56 th percentile [37–71]), healthy weight with chronic pain, obese without pain (BMI = 97 th percentile [95–99]), or the combination of obesity and chronic pain. Serum cortisol was lower with chronic pain and/or obesity compared to healthy controls and was lower with chronic pain and obesity compared to chronic pain alone (healthy weight). The lower serum cortisol in the pain alone group was more prominent in the morning compared to the afternoon. There was no relationship between serum estradiol and testosterone and study group. The decrease in the anti-inflammatory and other pain-ameliorating effects of cortisol may contribute to chronic pain and its resistance to treatment with concurrent obesity in female adolescents.